2021
DOI: 10.1001/jamaneurol.2020.2590
|View full text |Cite|
|
Sign up to set email alerts
|

Patient Assisted Intervention for Neuropathy: Comparison of Treatment in Real Life Situations (PAIN-CONTRoLS)

Abstract: and the Patient Assisted Intervention for Neuropathy: Comparison of Treatment in Real Life Situations (PAIN-CONTRoLS) Study Team IMPORTANCE Cryptogenic sensory polyneuropathy (CSPN) is a common generalized slowly progressive neuropathy, second in prevalence only to diabetic neuropathy. Most patients with CSPN have significant pain. Many medications have been tried for pain reduction in CSPN, including antiepileptics, antidepressants, and sodium channel blockers. There are no comparative studies that identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…A recent meta-analysis confirmed the limited efficacy of this treatment in recent randomized controlled trials (RCTs) [11]. In a Bayesian adaptive, open-label randomized clinical comparative effectiveness study, nortriptyline and duloxetine outperformed pregabalin when pain reduction and undesirable adverse effects were combined to a single end point for the treatment of chronic neuropathic pain [12]. In addition, the risk of misuse is also a major problem with pregabalin [13,14] and this drug is currently the most frequent cause of forged or falsified prescription [15].…”
Section: Pharmacological Treatmentsmentioning
confidence: 96%
“…A recent meta-analysis confirmed the limited efficacy of this treatment in recent randomized controlled trials (RCTs) [11]. In a Bayesian adaptive, open-label randomized clinical comparative effectiveness study, nortriptyline and duloxetine outperformed pregabalin when pain reduction and undesirable adverse effects were combined to a single end point for the treatment of chronic neuropathic pain [12]. In addition, the risk of misuse is also a major problem with pregabalin [13,14] and this drug is currently the most frequent cause of forged or falsified prescription [15].…”
Section: Pharmacological Treatmentsmentioning
confidence: 96%
“…One exception is the PAIN-CONTRoLS study, which compared 4 active medications for patients with cryptogenic neuropathy. 61 The study found that duloxetine and nortriptyline outperformed pregabalin and mexiletine. Comparable studies in PDN are also needed.…”
Section: Suggestions For Future Researchmentioning
confidence: 97%
“…Evoked pain includes hyperalgesia (abnormally increased pain sensation to a noxious stimulus) and allodynia (pain sensation to a non-noxious stimulus), which seriously affect a patient’s quality of life, incurring extreme economic burdens [ 5 ]. Currently prescribed pain relief treatments are still unsatisfactory or have limited effectiveness [ 6 ]. Therefore, many studies have attempted to elucidate the neuropathic pain mechanism and explore novel therapies for treating neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%